SISTEM EKONOMI INDONESIA DALAM PERSPEKTIF PANCASILA DAN UUD 1945 - Pratama, Agung Rifqi (Faculty of Law, Parahyangan Catholic University, 2018)
The focus of this article, using a juridical normatif and philosophical approach, is in tracking how Article 33 of the Indonesian Constitution is understood and how the Pancasila economic system (based on the five tenets of the State’s ideology) is being implemented by a number of exisitng economic policies. While the Article should be regarded as the embedodiment of Indonesian economic policy, it cannot be denied that the understanding of it evolved and changed following the 4thamendment to the Constitution. It is observed that the 4thamendment to the 1945 Constitution have had a great impact on the direction taken by the Indonesian economic policy makers. In using a juridical normative approach we are forced to take the position that Pancasila economic system as found in the Constitution should be followed by the letter in real economic policy making. On the other hand, just to do that, we cannot but realize the need for the existence of government political will.